Rapid FDI expansion of firms from emerging markets: evidence from Poland - Suk Yang, Oh; Niedzielska, Marcela Julia (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The conventional theory of gradual internationalization goes against the global trend of rapid foreign expansion as applied in particular to emerging markets. In this study we examine the conditions of rapid foreign direct investment (FDI) expansion that can be beneficial to firm performance. In order to do so we examine a firm’s internal factors, such as firm specific advantages (FSAs) and strategy, as well as external factors including domestic and foreign influences that moderate the relationship between firm performance and the speed of FDI expansion. By conducting empirical tests on data on Polish firms’ expansion, we find that some FSAs (profit per employee and foreign sales), as well as some aspects relevant to strategy (geographic and cultural distances), negatively influence the relationship between speed of FDI expansion and firm performance. From our results we conclude that Polish companies are unique in the way that neither gradual internationalization nor rapid foreign expansion amounts to a suitable strategy for them. The Polish market, exhibiting a combination of transition and emerging economy characteristics, must apply its own distinctive FDI strategy to compete in foreign markets
Argumenta Oeconomica, 2017, Nr 2 (39), s. 373-402
Keywords: FDI; speed of internationalization; emerging markets; multinational enterprises